Excavations and Researches at Tarquinia (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
This paper offers an overview of ongoing research and excavation carried out by the Università degli Studi di Milano on the Civita plateau of Tarquinia since 1982. The “Tarquinia Project” is a network of collaborations with Italian and international Universities and Institutions. Such an interdisciplinary approach is relevant to the training of those who take part in the whole project.
Keywords: Tarquinia; Civita; monumental complex